A full term abdominal pregnancy with an isthmic tubal implantation of the placenta - Sansan Rodrigue Sib; Issa Ouédraogo; Moussa Sanogo; Sibraogo Kiemtoré; Yobi Alexis Sawadogo; Hyacinthe Zamané; Blandine Bonané (BMC, 2018)
Abstract Background Abdominal pregnancy is defined as the partial or total insertion of the embryo into the abdominal cavity. It is rare, and can evolve towards the full term if it is not recognized in the early pregnancy. It carries a high risk of maternal-fetal morbidity and mortality. Case presentation We report a case of a 22 year-old gravida IV, para II with an asymptomatic and undiagnosed abdominal pregnancy presumed full term, in a context of health centers under-equipment. She had attended 5 routine antenatal care, but had not performed any ultrasound scan. She had been transferred from a medical center to the Hospital of Ouahigouya (Burkina Faso) for bowel sub-obstruction and intrauterine fetal death, with failure of labor induction. On admission, the hypothesis of uterine rupture or abdominal pregnancy with antepartum fetal demise was considered. A laparotomy was then performed, where an abdominal pregnancy was discovered, and a dead term baby weighing 3300 g delivered. The placenta which was implanted into the ruptured isthmus of the left fallopian tube was removed by salpingectomy. Postoperative follow-up was uneventful. Conclusion This case report exposes the necessity for the practitioner to think about the possibility of abdominal pregnancy in his clinical and sonographic practice, irrespective of the gestational age, mainly in contexts where there is under-equipment of the health centers.